INCREASING PUBLIC AWARENESS IN DRUG USE THROUGH SMART COMMUNITY MOVEMENT USING DRUGS (SCMUD) - Sandy Kurniajati; Indraningrum Fitria (Suluh Adiluhung Publisher (SAPub), 2024)
The community tends to try to overcome health problems through easier and more cost-efficient methods. This triggers the tendency of the community to self-medicate. Self-medication is the use of drugs by individuals, not based on a doctor's prescription, but based on the individual's initiative. This community service aims to increase awareness of using drugs through Smart Community Movement Using Drugs (SCMUD) in the Bulakdawung community, Parang village, Banyakan district, Kediri regency. The activity was carried out on May 17, 2024, by providing Health Counseling to mothers who accompany their children to study groups, with lecture and question and answer methods, the media used was the leaflet of awareness of using drugs. The results of the activity were 21 mothers with most elementary school education backgrounds (80.95%), work as housewives (95.23%), less knowledge about awareness of using drugs (71.42%), good attitudes awareness of using drugs (66.67%) and drug use behavior in the family (80.9%) and those lacking 19.1%. After being given health education regarding the safe use of drugs through the Smart Community Movement Using Drugs, the community increasingly understands and carries out awareness to avoid the negative impacts of self-medication and provide appropriate treatment for family members who are sick and utilize health service centers appropriately. It was concluded that the activity can increase public awareness in the use of drugs through health counseling.